Method for coating molybdenum disulfide protective layer on surface of titanium aviation fastener
By polishing and pulsed laser beam on the surface of titanium aviation fasteners and applying a composite coating containing molybdenum disulfide, the wear and corrosion problems of titanium aviation fasteners in high load and corrosion environments are solved, and their wear resistance and service life are significantly improved.
Patent Information
- Application Number
- CN202510396955.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-01
AI Technical Summary
Titanium aviation fasteners are prone to wear and tear in application scenarios with high load and frequent movement, and face corrosion risks under certain environmental conditions, resulting in a shorter service life.
By fine polishing the surface of titanium aviation fasteners and pulsed laser beams to form a honeycomb micropore array, increasing the surface area and coating adhesion points, and applying a composite coating containing molybdenum disulfide, combined with a hydrophobic protective layer to improve the adhesion, wear resistance and corrosion resistance of the coating.
It significantly improves the wear resistance and service life of titanium aerospace fasteners, meets the high requirements for durability and reliability in the aerospace field, and simplifies the processing process through the design of composite coatings.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal protection, and more specifically, to a method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener. Background Art
[0002] In the aerospace field, titanium and its alloys are widely used in the manufacture of various key components, especially fasteners, due to their excellent strength-to-weight ratio, excellent corrosion resistance and biocompatibility. However, titanium aviation fasteners face multiple challenges in actual use, which are mainly due to their specific service environment and application requirements.
[0003] First, although titanium alloy has high mechanical strength, its surface hardness is relatively low, which makes it prone to wear in high-load and frequent motion applications. Especially in high-temperature environments, the wear resistance of titanium alloy will decrease significantly, increasing the risk of component failure. Therefore, how to effectively reduce the friction coefficient of titanium aviation fasteners and improve their wear resistance has become a key issue that needs to be solved urgently.
[0004] Secondly, although titanium alloy itself has good corrosion resistance, under certain special environmental conditions, such as humid environment containing chloride ions, titanium alloy may still suffer from serious problems such as local corrosion or stress corrosion cracking. In addition, when titanium alloy contacts with other metals, galvanic corrosion may also occur, further increasing the risk of material damage. Therefore, it is very important to take effective anti-corrosion measures to extend the service life of titanium aviation fasteners. Summary of the invention
[0005] In order to improve the wear resistance and corrosion resistance of aviation fasteners, the present application provides a method for coating a molybdenum disulfide protective layer on the surface of titanium aviation fasteners.
[0006] The present application provides a method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which adopts the following technical solution: A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener comprises the following steps: S1. Fastener surface treatment: The fastener surface is polished to obtain a fastener with a surface roughness of 0.05-0.07 microns. After cleaning with an organic solvent, a pulsed laser beam is used to form a honeycomb micropore array on the fastener surface with a pore diameter of 5-10 μm and a depth of 20-50 μm to obtain a pre-treated fastener; S2. Applying a molybdenum disulfide coating: applying a molybdenum disulfide coating on the pretreated surface of the fastener, storing it at room temperature for 12 hours, and then applying a hydrophobic protective layer; S3. Room temperature curing: Curing the fasteners coated with the hydrophobic protective layer at room temperature for 4-6 hours.
[0007] By adopting the above technical solution, the surface of the fastener is finely polished and a honeycomb micropore array is created using a pulsed laser beam to increase the surface area and coating attachment points, thereby significantly improving the adhesion and uniformity of the coating. Next, a coating containing molybdenum disulfide is applied, and a hydrophobic protective layer is applied thereon. This not only utilizes the characteristics of molybdenum disulfide as a solid lubricant to reduce the friction coefficient and enhance wear resistance, but also further improves corrosion resistance and water resistance through the hydrophobic layer. Finally, the curing treatment is carried out at room temperature to ensure that the coating can achieve optimal physical and chemical stability without destroying its structure. The design of this composite coating significantly enhances the wear resistance, corrosion resistance and service life of titanium aviation fasteners, while simplifying the processing process, making it more suitable for use in the aerospace field where durability and reliability are extremely high requirements.
[0008] Optionally, the molybdenum disulfide coating contains 20-30 parts of polyimide resin, 8-12 parts of molybdenum disulfide, 1-2 parts of aminosilane coupling agent, 0.5-1.5 parts of titanate coupling agent, 20-25 parts of 1-butyl-3-methylimidazole hexafluorophosphate, 5-8 parts of graphene oxide, and 0.5-0.8 parts of benzotriazole.
[0009] By adopting the above technical solution, polyimide resin is used as a high temperature resistant matrix to provide mechanical strength and film-forming properties; molybdenum disulfide reduces wear through a layered slip structure, and its surface is modified by an aminosilane coupling agent to enhance the interface bonding with the resin through the -Si-O-Mo bond; the titanane coupling agent bridges the graphene oxide and the resin, and utilizes the two-dimensional interpenetrating structure of GO (graphene oxide) to improve the load-bearing capacity and inhibit the MoS 2 (MoS2) oxidation; Benzotriazole adsorbs on the metal surface to form a passivation film, which cooperates with the GO physical barrier to block the corrosion path. The core mechanism is "resin matrix-lubrication enhancement-interface bonding-anti-corrosion synergy", which comprehensively realizes the integrated performance of high wear resistance, high temperature resistance and long-term anti-corrosion.
[0010] Optionally, the preparation of the molybdenum disulfide coating comprises the following steps: (1) dispersing molybdenum disulfide and an aminosilane coupling agent in ethanol, ultrasonically treating the mixture, centrifugally separating, washing, and drying the mixture to obtain pretreated molybdenum disulfide; (2) mixing graphene oxide and a titanane coupling agent and ball milling to obtain pretreated graphene oxide; (3) Dissolve the polyimide resin in 1-butyl-3-methylimidazole hexafluorophosphate, heat to 55-65°C and stir until completely dissolved, add the pretreated molybdenum disulfide, graphene oxide and benzotriazole in sequence, and disperse evenly by ultrasonication to obtain a slurry, which is the molybdenum disulfide coating.
[0011] By adopting the above technical scheme, molybdenum disulfide and aminosilane coupling agent are first ultrasonically dispersed in ethanol and centrifugally washed and dried to enhance the interfacial bonding force between them and the resin matrix; at the same time, graphene oxide and titanane coupling agent are ball milled to improve the dispersibility and compatibility of graphene oxide with the matrix. Subsequently, in the process of dissolving polyimide resin in ionic liquid (1-butyl-3-methylimidazole hexafluorophosphate), pretreated molybdenum disulfide, graphene oxide and benzotriazole are added in sequence, and ultrasonic dispersion is performed to form a uniform slurry to obtain a molybdenum disulfide coating with good wear resistance and durability.
[0012] Optionally, the hydrophobic protective layer comprises the following raw materials in parts by weight: 3-5 parts of fluorosilane compounds, 1-2 parts of glycidoxypropyltrimethoxysilane, 5-8 parts of perfluoropolyether, 10-15 parts of hydrofluoroether, and 0.5-1 part of methyltrimethoxysilane.
[0013] By adopting the above technical solutions, fluorosilane compounds provide low surface energy through long fluorocarbon chains, and perfluoropolyether dynamically wets and fills micropores and reduces the friction coefficient. The two work together to construct a super-hydrophobic state; glycidoxypropyltrimethoxysilane and methyltrimethoxysilane form a dense Si-O-Si network through hydrolysis and condensation reaction. The former's epoxy group reacts with the underlying polyimide to enhance the interface bonding, and the latter accelerates cross-linking and shortens the curing time; hydrofluoroether is used as a solvent to regulate viscosity, and after volatilization, it induces fluorosilane and perfluoropolyether to align in a directional manner to form a micro-nano rough structure. The core mechanism is "low surface energy + micro-nano structure + strong interface bonding", which ultimately achieves multifunctional protection with wear resistance and corrosion resistance.
[0014] Optionally, the fluorosilane compound is tridecafluorooctyltrimethoxysilane.
[0015] By adopting the above technical solution, tridecafluorooctyltrimethoxysilane has ultra-low surface energy, which can give the protective layer surface excellent hydrophobic properties. At the same time, its short carbon chain structure helps to improve its solubility in solvents, thereby effectively avoiding the occurrence of crystallization problems. Tridecafluorooctyltrimethoxysilane works synergistically with glycidoxypropyltrimethoxysilane and methyltrimethoxysilane in the formula to jointly construct a dense Si-O-Si network structure. This structure not only significantly enhances the overall stability and mechanical strength of the coating, but also greatly improves the interfacial bonding strength between the coating and the underlying molybdenum disulfide coating.
[0016] Optionally, during the pulse laser beam treatment, nitrogen is used as a carrier gas and hydrogen sulfide gas with a volume concentration of 5-10% is introduced.
[0017] By adopting the above technical solution, hydrogen sulfide gas decomposes into active sulfur atoms and hydrogen under high temperature of laser. The sulfur atoms react with the surface of titanium alloy to form a nano-scale titanium sulfide layer, which significantly improves its wear resistance. At the same time, the sulfur atoms form Ti-S-Mo chemical bonds with the subsequently applied molybdenum disulfide coating to improve the bonding strength of the coating. The honeycomb micropore array enhances the shear resistance of the molybdenum disulfide coating through a mechanical interlocking effect and stores sulfides as a self-lubricating reserve. Nitrogen inhibits the oxidation of the titanium surface and maintains the purity of the vulcanization reaction, thereby improving the friction and corrosion resistance of the fastener surface.
[0018] Optionally, the molybdenum disulfide coating is applied at a temperature of 70-90°C.
[0019] By adopting the above technical solution, when heated to 70-90°C, the π electrons in the graphene oxide in the coating and the positrons in the ionic liquid induce the ionic liquid molecules to arrange into a loose structure through the π-π stacking effect, which significantly reduces the overall viscosity of the coating. This helps it to form a smoother and continuous coating on the substrate, achieve a more uniform and delicate coating effect, and reduce the possibility of internal defects in the coating. After the temperature drops, the material will return to a viscous state, and the molybdenum disulfide particles will be neatly arranged and fixed on the surface of the material. This vertically arranged structure greatly improves the lubrication performance of the coating and improves the wear resistance of the material.
[0020] Optionally, the molybdenum disulfide coating further includes 1-3 parts of hydroxy magnesium silicate.
[0021] By adopting the above technical solution, hydroxy magnesium silicate has a layered silicate structure, which can synergize with the hexagonal lattice of molybdenum disulfide to further reduce the friction coefficient and improve the load-bearing capacity of the coating.
[0022] In summary, this application has the following beneficial effects: 1. This application greatly increases the contact area and attachment points between the coating and the substrate by finely pre-treating the surface of titanium aviation fasteners and combining it with a honeycomb micropore array formed by a pulsed laser beam, significantly improving the adhesion and uniformity of the coating. Applying a composite coating containing high-performance materials such as molybdenum disulfide and applying a hydrophobic protective layer on it not only utilizes the solid lubrication properties of molybdenum disulfide, but also improves the corrosion resistance and waterproof performance through the hydrophobic layer. With the combined effect of these measures, the wear resistance and service life of titanium aviation fasteners have been significantly improved, meeting the extremely high requirements for durability and reliability in the aerospace field.
[0023] 2. In this application, polyimide resin, graphene oxide, magnesium hydroxysilicate and other ingredients are added to the molybdenum disulfide coating, and their excellent mechanical strength and layered sliding properties are used to significantly reduce the friction coefficient and wear rate. At the same time, the introduction of the hydrophobic protective layer, especially fluorosilane compounds, perfluoropolyether and other ingredients, gives the coating ultra-low surface energy and excellent waterproof performance, effectively preventing the intrusion of moisture and other corrosive media, and delaying the MoS 2 oxidative degradation process.
[0024] 3. The method of the present application, when the molybdenum disulfide coating is applied at 70-90°C, the overall viscosity of the coating is significantly reduced, which helps to form a smoother and more continuous coating and reduce the possibility of internal defects. After cooling, the material returns to a viscous state, and the molybdenum disulfide particles are neatly arranged and fixed on the surface of the material, thereby greatly improving the wear resistance of the coating. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0027] Molybdenum disulfide particle size 1-2μm, purity >99%, CAS: 1317-33-5; 1-butyl-3-methylimidazolium hexafluorophosphate was purchased from Hubei Xingyan New Materials Technology Co., Ltd., CAS: 174501-64-5; diamond polishing liquid was purchased from Shanghai Shuangjin Electronic Technology Co., Ltd.; Preparation Example
[0028] Preparation Example 1 A molybdenum disulfide coating, the preparation of which comprises the following steps: (1) Disperse 1 kg of molybdenum disulfide and 0.15 kg of γ-aminopropyltriethoxysilane (aminosilane coupling agent) in 20 L of ethanol, perform ultrasonic treatment at 500 W and 40 kHz for 30 min, remove the supernatant by centrifugation, wash the precipitate with ethanol for 2-3 times, and obtain pretreated molybdenum disulfide after drying; (2) 0.5 kg of graphene oxide and 0.05 kg of isopropyl tri(dioctyl pyrophosphate) titanate were mixed and added to a ball mill, and 3 mm zirconium oxide balls were used as ball milling media. After ball milling at 400 rpm / min for 2 h, the mixture was washed with deionized water and centrifuged to obtain pretreated graphene oxide. (3) Dissolve 2.5 kg of polyimide resin in 2 kg of 1-butyl-3-methylimidazole hexafluorophosphate solution, heat to 60 ° C and stir until completely dissolved, add pretreated molybdenum disulfide and graphene oxide and 0.05 kg of benzotriazole in sequence, and obtain the molybdenum disulfide coating after ultrasonic dispersion.
[0029] Preparation Example 2 A molybdenum disulfide coating, the preparation of which comprises the following steps: (1) Disperse 0.8 kg of molybdenum disulfide and 0.1 kg of γ-aminopropyltriethoxysilane (aminosilane coupling agent) in 20 L of ethanol, perform ultrasonic treatment at 500 W and 40 kHz for 30 min, remove the supernatant by centrifugation, wash the precipitate with ethanol for 2-3 times, and obtain pretreated molybdenum disulfide after drying; (2) 0.8 kg of graphene oxide and 0.15 kg of isopropyl tri(dioctyl pyrophosphate) titanate were mixed and added into a ball mill, 3 mm zirconium oxide balls were used as ball milling media, ball milling was performed at 400 rpm / min for 2 h, and then washed with deionized water, and centrifuged and dried to obtain pretreated graphene oxide; (3) 2 kg of polyimide resin was dissolved in 2.25 kg of 1-butyl-3-methylimidazole hexafluorophosphate solution, heated to 65 °C and stirred until completely dissolved, and the pretreated molybdenum disulfide and graphene oxide and 0.065 kg of benzotriazole were added in sequence, and the molybdenum disulfide coating was obtained after ultrasonic dispersion.
[0030] Preparation Example 3 A molybdenum disulfide coating, the preparation of which comprises the following steps: (1) 1.2 kg of molybdenum disulfide and 0.2 kg of γ-aminopropyltriethoxysilane (aminosilane coupling agent) were dispersed in 20 L of ethanol, and ultrasonically treated at 500 W and 40 kHz for 30 min. The supernatant was removed by centrifugation, and the precipitate was washed 2-3 times with ethanol, and dried to obtain pretreated molybdenum disulfide; (2) 0.65 kg of graphene oxide and 0.1 kg of isopropyl tri(dioctyl pyrophosphate) titanate were mixed and added to a ball mill, and 3 mm zirconium oxide balls were used as ball milling media. After ball milling at 400 rpm / min for 2 h, the mixture was washed with deionized water and centrifuged and dried to obtain pretreated graphene oxide; (3) 3 kg of polyimide resin was dissolved in 2.5 kg of 1-butyl-3-methylimidazole hexafluorophosphate solution, heated to 55 °C and stirred until completely dissolved, and the pretreated molybdenum disulfide and graphene oxide and 0.08 kg of benzotriazole were added in sequence, and the molybdenum disulfide coating was obtained after ultrasonic dispersion.
[0031] Preparation Example 4 A molybdenum disulfide coating, which is different from Preparation Example 1 in that 0.1 kg of magnesium hydroxysilicate is added in this Preparation Example, and the preparation comprises the following steps: (1) Disperse 1 kg of molybdenum disulfide and 0.15 kg of γ-aminopropyltriethoxysilane (aminosilane coupling agent) in 20 L of ethanol, perform ultrasonic treatment at 500 W and 40 kHz for 30 min, remove the supernatant by centrifugation, wash the precipitate with ethanol for 2-3 times, and obtain pretreated molybdenum disulfide after drying; (2) 0.5 kg of graphene oxide and 0.05 kg of isopropyl tri(dioctyl pyrophosphate) titanate were mixed and added to a ball mill, and 3 mm zirconium oxide balls were used as ball milling media. After ball milling at 400 rpm / min for 2 h, the mixture was washed with deionized water and centrifuged to obtain pretreated graphene oxide. (3) Dissolve 2.5 kg of polyimide resin in 2 kg of 1-butyl-3-methylimidazole hexafluorophosphate solution, heat to 60 ° C and stir until completely dissolved, add pretreated molybdenum disulfide and graphene oxide, 0.05 kg of benzotriazole, and 0.1 kg of hydroxy magnesium silicate in sequence, and obtain the molybdenum disulfide coating after ultrasonic dispersion.
[0032] Preparation Example 5 A molybdenum disulfide coating, which is different from Preparation Example 4 in that 0.2 kg of hydroxy magnesium silicate is added in this Preparation Example.
[0033] Preparation Example 6 A molybdenum disulfide coating, which is different from Preparation Example 4 in that 0.3 kg of hydroxy magnesium silicate is added in this Preparation Example.
[0034] Example
[0035] Example 1
[0036] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, specifically comprising the following steps: S1. Fastener surface treatment: Use diamond polishing liquid with a particle size of 0.5μm to mechanically polish the surface of TC4 titanium alloy screw fasteners to obtain fasteners with a surface roughness of 0.06μm, use acetone and anhydrous ethanol for ultrasonic cleaning in sequence, and after drying, use a pulsed laser beam (wavelength 1064nm, pulse width 100ns, power 80w) in a nitrogen and 8vol% hydrogen sulfide mixed atmosphere to form a honeycomb micropore array on the material surface with a pore size of 8μm and a depth of 35μm to obtain pre-treated fasteners; S2. Coating of molybdenum disulfide coating: Heat the molybdenum disulfide coating slurry prepared in Preparation Example 1 to 80°C, and use a high-pressure airless spray gun to spray it onto the surface of the screw preheated to 80°C, with a wet film thickness of 60 μm. After standing at room temperature for 12 hours, spray a hydrophobic protective layer with a wet film thickness of 20 μm; the hydrophobic layer includes: 4 kg of tridecafluorooctyltrimethoxysilane (fluorosilane compound), 1.5 kg of glycidoxypropyltrimethoxysilane, 8 kg of perfluoropolyether, 12.5 kg of hydrofluoroether, and 0.65 kg of methyltrimethoxysilane; S3. Room temperature curing: The screw fasteners coated with the hydrophobic protective layer are cured at room temperature for 5 hours to obtain titanium aviation fasteners with a molybdenum disulfide protective layer coated on the surface.
[0037] Example 2
[0038] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, specifically comprising the following steps: S1. Fastener surface treatment: Use diamond polishing liquid with a particle size of 0.5μm to mechanically polish the surface of TC4 titanium alloy screw fasteners to obtain fasteners with a surface roughness of 0.07μm, use acetone and sewage ethanol ultrasonic cleaning in turn, and after drying, use a pulsed laser beam (wavelength 1064nm, pulse width 100ns, power 80w) in a nitrogen and 5vol% hydrogen sulfide mixed atmosphere to form a honeycomb micropore array on the material surface with a pore size of 10μm and a depth of 50μm to obtain pre-treated fasteners; S2. Coating of molybdenum disulfide coating: The molybdenum disulfide coating slurry prepared in Preparation Example 2 was heated to 70°C, and sprayed onto the surface of the fastener preheated to 70°C using a high-pressure airless spray gun, with a wet film thickness of 60 μm. After standing at room temperature for 12 hours, a hydrophobic protective layer was sprayed, and the wet film thickness of the hydrophobic protective layer was 20 μm; the hydrophobic layer included: 3 kg of tridecafluorooctyltrimethoxysilane (fluorosilane compound), 2 kg of glycidoxypropyltrimethoxysilane, 5 kg of perfluoropolyether, 10 kg of hydrofluoroether, and 0.5 kg of methyltrimethoxysilane; S3. Room temperature curing: The fastener coated with the hydrophobic protective layer is cured at room temperature for 6 hours to obtain a titanium aviation fastener with a molybdenum disulfide protective layer coated on the surface.
[0039] Example 3
[0040] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, specifically comprising the following steps: S1. Fastener surface treatment: Use diamond polishing liquid with a particle size of 0.5μm to mechanically polish the surface of TC4 titanium alloy screw fasteners to obtain fasteners with a surface roughness of 0.05μm, use acetone and sewage ethanol ultrasonic cleaning in turn, and after drying, use a pulsed laser beam (wavelength 1064nm, pulse width 100ns, power 80w) in a nitrogen and 10vol% hydrogen sulfide mixed atmosphere to form a honeycomb micropore array on the material surface with a pore size of 5μm and a depth of 20μm to obtain pre-treated fasteners; S2. Coating of molybdenum disulfide coating: The molybdenum disulfide coating slurry prepared in Preparation Example 3 was heated to 90°C, and sprayed onto the surface of the fastener preheated to 90°C using a high-pressure airless spray gun, with a wet film thickness of 60 μm. After standing at room temperature for 12 hours, a hydrophobic protective layer was sprayed, and the wet film thickness of the hydrophobic protective layer was 20 μm; the hydrophobic layer included: 5 kg of tridecafluorooctyltrimethoxysilane (fluorosilane compound), 1 kg of glycidoxypropyltrimethoxysilane, 6.5 kg of perfluoropolyether, 15 kg of hydrofluoroether, and 1 kg of methyltrimethoxysilane; S3. Room temperature curing: The fastener coated with the hydrophobic protective layer is cured at room temperature for 4 hours to obtain a titanium aviation fastener with a molybdenum disulfide protective layer coated on the surface.
[0041] Example 4
[0042] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that the fluorosilane compound added to the hydrophobic protective layer in this embodiment is trityl fluorosilane.
[0043] Example 5
[0044] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener is different from Example 1 in that nitrogen is introduced when the fastener is pretreated with a pulsed laser beam in this embodiment.
[0045] Example 6
[0046] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener is different from Example 1 in that the molybdenum disulfide coating is coated at 50° C. in this embodiment.
[0047] Example 7
[0048] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener is different from Example 1 in that the molybdenum disulfide coating is coated at 100° C. in this embodiment.
[0049] Example 8
[0050] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that the molybdenum disulfide coating coated in this example is prepared in Preparation Example 4.
[0051] Example 9
[0052] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that the molybdenum disulfide coating coated in this example is prepared in Preparation Example 5.
[0053] Example 10
[0054] A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that the molybdenum disulfide coating coated in this example is prepared in Preparation Example 6.
[0055] Comparative Example
[0056] Comparative Example 1 A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that a pulsed laser beam is not used to treat the material surface in this comparative example.
[0057] Comparative Example 2 A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that graphene oxide and titanane coupling agent are not added to the molybdenum disulfide coating of this comparative example.
[0058] Comparative Example 3 A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that an equal amount of methanol is used to replace 1-butyl-3-methylimidazole hexafluorophosphate in the molybdenum disulfide coating of this comparative example.
[0059] Comparative Example 4 A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, which is different from Example 1 in that no aminosilane coupling agent and titanane coupling agent are added to the molybdenum disulfide coating of this comparative example.
[0060] Performance testing Detection Methods
[0061] Friction test: The sliding wear test was carried out using an MMU-10G high-temperature end face friction and wear tester with a speed of 200 r / min and a load of 10 N to test the friction coefficient. High temperature durability: After heat treatment at 300℃ for 2h, the friction coefficient is tested again and the rate of change of the friction coefficient is recorded; Corrosion resistance: According to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", the time for no white corrosion products to appear in the neutral salt spray test is recorded.
[0062] Table 1 Test results
[0063] Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that pretreatment of the material surface with a pulsed laser beam can enhance the mechanical interlocking effect between the coating and the substrate by forming a honeycomb micropore array, thereby improving the adhesion of the coating and thus improving the corrosion resistance and durability of the coating.
[0064] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2, indicating that adding graphene oxide treated with a titanane coupling agent to the molybdenum disulfide coating can improve the wear resistance of the coating through interfacial chemical bonding and the synergistic effect of the two-dimensional sheets.
[0065] Combining Examples 1-3 and Comparative Example 3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3. Failure to add 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid results in an increase in the viscosity of the dispersion system and microcracks in the coating, resulting in a significant decrease in corrosion resistance and durability.
[0066] Combining Examples 1-3 and Comparative Example 4 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 4. When aminosilane coupling agent and titanane coupling agent are not added, better interface bonding cannot be formed between the raw materials of the coating, resulting in a decrease in its various performances.
[0067] Combining Example 1 with Example 4 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 4, indicating that selecting tridecafluorooctyltrimethoxysilane as a fluorosilane compound to be added to the hydrophobic protective layer can form a denser low surface energy film and significantly inhibit Cl - Penetration improves the corrosion resistance of the coating.
[0068] Combining Example 1 with Example 5 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 5. The addition of hydrogen sulfide gas can generate titanium sulfide in situ during laser irradiation, thereby enhancing the friction resistance of the coating.
[0069] Combining Example 1 with Examples 6-7 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Examples 6-7, indicating that the control of temperature when coating the molybdenum disulfide coating will affect the performance of the final coating. At an appropriate temperature, the ionic liquid in the molybdenum disulfide coating is neatly arranged with graphene oxide to form a smooth and continuous coating, thereby improving the wear resistance of the material.
[0070] Combining Example 1 with Examples 8-10 and Table 1, it can be seen that the experimental data of Examples 8-10 are better than those of Example 1, indicating that adding hydroxy magnesium silicate to the molybdenum disulfide coating can synergistically act with molybdenum disulfide to reduce the friction coefficient and improve the wear resistance of the material.
[0071] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener, characterized in that: The steps include: S1. Fastener surface treatment: The fastener surface is polished to obtain a fastener with a surface roughness of 0.05-0.07 microns. After cleaning with an organic solvent, a pulsed laser beam is used to form a honeycomb micropore array on the fastener surface with a pore diameter of 5-10 μm and a depth of 20-50 μm to obtain a pre-treated fastener; S2. Applying a molybdenum disulfide coating: applying a molybdenum disulfide coating on the pretreated surface of the fastener, storing it at room temperature for 12 hours, and then applying a hydrophobic protective layer; S3. Room temperature curing: Curing the fasteners coated with the hydrophobic protective layer at room temperature for 4-6 hours.
2. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 1, characterized in that: The molybdenum disulfide coating contains the following raw materials in parts by weight: 20-30 parts of polyimide resin, 8-12 parts of molybdenum disulfide, 1-2 parts of aminosilane coupling agent, 0.5-1.5 parts of titanane coupling agent, 20-25 parts of 1-butyl-3-methylimidazole hexafluorophosphate, 5-8 parts of graphene oxide, and 0.5-0.8 parts of benzotriazole.
3. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 1, characterized in that: The molybdenum disulfide coating preparation comprises the following steps: (1) dispersing molybdenum disulfide and an aminosilane coupling agent in ethanol, ultrasonically treating the mixture, centrifugally separating, washing, and drying the mixture to obtain pretreated molybdenum disulfide; (2) mixing graphene oxide and a titanane coupling agent and ball milling to obtain pretreated graphene oxide; (3) Dissolve the polyimide resin in 1-butyl-3-methylimidazole hexafluorophosphate, heat to 55-65°C and stir until completely dissolved, add the pretreated molybdenum disulfide, graphene oxide and benzotriazole in sequence, and disperse evenly by ultrasonication to obtain a slurry, which is the molybdenum disulfide coating.
4. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 1, characterized in that: The hydrophobic protective layer comprises the following raw materials in parts by weight: 3-5 parts of fluorosilane compounds, 1-2 parts of glycidoxypropyltrimethoxysilane, 5-8 parts of perfluoropolyether, 10-15 parts of hydrofluoroether, and 0.5-1 part of methyltrimethoxysilane.
5. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 4, characterized in that: The fluorosilane compound is tridecafluorooctyltrimethoxysilane.
6. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 1, characterized in that: During the pulse laser beam treatment, nitrogen was used as a carrier gas, and hydrogen sulfide gas with a volume concentration of 5-10% was introduced.
7. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 1, characterized in that: The coating of the molybdenum disulfide coating is carried out at a temperature of 70-90°C.
8. The method for coating a molybdenum disulfide protective layer on the surface of a titanium aviation fastener according to claim 2, characterized in that: The molybdenum disulfide coating also includes 1-3 parts of hydroxy magnesium silicate.
Citation Information
Patent Citations
Use of ionic liquids for improving the properties of lubricating compositions
CN101688144A
Preparing method of graphene / molybdenum disulfide containing titanium and titanium alloy surface self-lubricating abrasion resisting coating
CN108187990A
Light-cured coating, ultraviolet-curable hydrophobic anti-adhesive film surface and preparation method thereof
CN109181521A
High-temperature-resistant conductive lubricating grease used for copper-plating-free special coating solid welding wire
CN112247401A
Lubricating anti-attrition coating special for aluminum alloy and preparation method and application thereof
CN114672219A